Acute kidney injury and its outcome in obstetrics - Shah, Dipal C.; Patel, Babulal S.; Shah, Akshay C.; Jani, Shashwat K.; Agrawal, Saumya P.; Patel, Vismay B.; Patel, Adwait B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Acute kidney injury occurring during pregnancy, labour, delivery, and/or postpartum period. Proper management of AKI (acute kidney injury) is challenging because (i) both maternal and fetal health must be considered and (ii) the cardiovascular and renal adaptations of pregnancy add to the complexity for management. Methods: The objective of this study was to study association and contributing factors in AKI, a retrospective study of 20 cases of AKI complicating pregnancies carried out in department of obstetrics and gynecology, SVPIMSR over a period of 12 months and results were studied and analysed. Etiological factors, associated liver pathology, coagulation abnormality, thrombocytopenia, sepsis, recovery status and fetomaternal outcome were studied and tabulated. AKI was analysed in terms of maximal stage of renal injury attained as per risk, injury, failure, loss of function, and end-stage renal disease (RIFLE) criteria. Results: The incidence of ARF (acute renal failure) in pregnancy was about 0.3%. Hypertensive disorders were the major causative factor. Amongst the 20 cases, 8 cases were referred from outside and two of them died. Total 5 of 20 cases required hemodialysis and two of them had partial recovery. Conclusions: AKI complicating pregnancies are not uncommon. If recognized and treated promptly, recovery is assured in majority of cases. Early identification and prompt management of pre-eclampsia and sepsis can prevent majority of cases. Ultrasonography revelation of placenta previa or abruption helps in early management eventually decreases the chances of bleeding which is one of the causes of AKI (pre-renal cause).